Crisis, Identity, and Intoxication: Youth Drug Abuse and Socio-Economic Marginalization in Post-2000s Zimbabwe - Nyatsanza, Ruvimbo; Nyoni, Farai Tendai; Chiremba, Takudzwa (Baileo: Jurnal Sosial Humaniora, 2025)
Drug and substance abuse among Zimbabwean youth in the post-2000 era has reached an alarming crisis level. This study aims to examine emerging trends in substance abuse practices among young people and to evaluate the effectiveness of existing intervention measures. Using a documentary survey method that draws on policy reports, media sources, and public records, the study investigates the strong link between acute socio-economic marginalization and the rise of increasingly creative yet hazardous substance consumption practices. Key findings indicate that while cannabis remains the most commonly abused substance, new and unconventional patterns have emerged. These include the misuse of prescription drugs, consumption of home-brewed intoxicants, transfusion of drug users’ blood, ingestion of drug-laced foods, and even the intake of sodium polyacrylate extracted from boiled baby diapers. The study highlights poverty, structural unemployment, and weak border surveillance as major driving forces. Despite various efforts by government authorities and law enforcement, current policy responses appear inadequate in addressing the evolving dynamics of the problem. The novelty of this study lies in its documentation of underreported forms of substance use and its analysis of how these practices relate to youth identity formation in the context of prolonged crisis. The study recommends an interdisciplinary and participatory approach to social policy, one that moves beyond punitive measures to include social rehabilitation, inclusive economic development, and the strengthening of positive youth identities. This research contributes to the broader field of social sciences and humanities, particularly in understanding the intersections of crisis, identity, and deviance within the Global South.